2004
DOI: 10.1128/jb.186.14.4520-4527.2004
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in the Receptor-Binding Domain of the Enzymatic Colicin E9 Is Required for Toxicity against Escherichia coli Cells

Abstract: The events that occur after the binding of the enzymatic E colicins to Escherichia coli BtuB receptors that lead to translocation of the cytotoxic domain into the periplasmic space and, ultimately, cell killing are poorly understood. It has been suggested that unfolding of the coiled-coil BtuB receptor binding domain of the E colicins may be an essential step that leads to the loss of immunity protein from the colicin and immunity protein complex and then triggers the events of translocation. We introduced pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 37 publications
(50 reference statements)
2
44
0
Order By: Relevance
“…This implies structural modifications starting from the receptor binding domain (237,607). This suggestion correlates with the inactivity of oxidized forms of double-cysteine mutants that lock the colicin E9 reception domain without interfering with its capacity to interact with the BtuB receptor (513). Overall, these data suggest that the unfolding of the receptor binding domain is necessary for starting the translocation process.…”
Section: Tol-dependent Colicinsmentioning
confidence: 64%
See 2 more Smart Citations
“…This implies structural modifications starting from the receptor binding domain (237,607). This suggestion correlates with the inactivity of oxidized forms of double-cysteine mutants that lock the colicin E9 reception domain without interfering with its capacity to interact with the BtuB receptor (513). Overall, these data suggest that the unfolding of the receptor binding domain is necessary for starting the translocation process.…”
Section: Tol-dependent Colicinsmentioning
confidence: 64%
“…Data are available concerning structural modifications of colicins or Tol subunits during the transit step, suggesting that it is not a passive process involving sequential interactions with cell envelope components but rather that it is a dynamic process involving conformational changes of both the machinery components and the ligand. First, it has been shown that the colicin A central domain remains in an interaction with the BtuB receptor while both N-and C-terminal domains are translocated (24, 165,513). This implies that the three domains are linked via flexible regions that are subject to large-scale structural modifications.…”
Section: Tol-dependent Colicinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein contains two cysteine mutations in the ColE9 receptor-binding domain that, in the reduced protein, do not affect its colicin activity. Formation of a disulfide bond under oxidizing conditions leads to loss of biological activity, as previously described (22). Plasmid pAG1 is derived from pML261 and contains a 2.4-kb EcoRIHindIII fragment that encodes the complete btuB gene in the vector pUC8 (15).…”
Section: Methodsmentioning
confidence: 99%
“…(ii) Synchronized cell death using a "disulfide-locked" colicin E9 protein. We recently presented data showing that a mutant ColE9 protein (BH29) with an engineered disulfide bond in its receptor-binding domain (via two strategically positioned cysteine mutations) was inactive in the oxidized form and that activity was restored when it was reduced through the addition of DTT (22). The current reporter assay, because of its faster response time and sensitivity, enabled us to probe the early events after DTT addition.…”
Section: Applications Of the Assay (I) Protection By Various Immunitmentioning
confidence: 99%